Investigasi Minat dan Motivasi Belajar Matematika Siswa SMP dalam Pembelajaran Daring di Era Pandemic Covid-19 - Silalahi, Lulu Brygita; Sihombing, Susi; Purba, Tuty Novelinda; Marpaung, Riko Kurniawan; Sinaga, Wita; Tambunan, Hardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to investigate the interest and motivation in learning mathematics for junior high school students during online learning during the Covid-19 pandemic in depth and to explore the faktors that influence students' interest and motivation in learning using triangulation techniques, namely observation and interviews. This research uses descriptive qualitative research method with the type of case study research. This research was conducted at SMP Negeri II Dolok Pardamean, Simalungun Regency. The population in this study were all seventh grade students for the 2020/2021 academic year at SMP Negeri II Dolok Pardamean. The sample used was all students of class VII-1, then 3 students were selected for the 2020/2021 academic year. Based on the results and discussion of the research, it shows that most of the seventh grade students of SMP Negeri II Dolok Pardamean have high interest and motivation in learning mathematics, which is indicated by the average percentage of students' interest and motivation in learning mathematics, which is 76.46%. In conclusion, online learning that has been carried out at SMP Negeri II Dolok Pardamean has succeeded in increasing interest and motivation in learning mathematics for grade VII-1 students and is in the high category. The success faktor in increasing students' interest and motivation in learning is influenced by teachers and students' family support. Keywords: Online learning, interest in learning, students' motivation to learn mathematics, the covid-19 pandemic